Physiological and performance characteristics of elite mountain bike cyclists - Linaker, K. (University of Canberra, 2004)
Cross-country (XC) mountain bike (MTB) riding is a new cycling discipline and research examining the physiological demands of MTB racing is limited. The purpose of this study was to comprehensively measure physiological characteristics, to identify the performance demands of XC and time trial (TT) MTB racing and to simulate a field MTB race in the laboratory to measure the physiological responses associated with racing. Twelve male and four female elite MTB cyclists volunteered to take part in this study. Subjects completed maximal aerobic power and, anaerobic power and capacity tests. MTB race data was collected during TT and XC competitions with SRM MTB power cranks fitted to the subjects MTB. Five male MTB cyclists (V . O2max 72.0 +/- 4.6 ml/kg/min-1, maximum power output (MPO) 5.40 +/- 0.30 W/kg-1, maximum heart rate (HRmax) 189 +/- 7 bpm) performed two laps of a MTB course in the field using their race bikes with MTB SRM power cranks fitted. A laboratory MTB race simulation was performed using a wind braked ergometer. Cyclists attempted to match the average and peak power output (W/kg-1) achieved in the field trial in the laboratory. Power output (PO), heart rate (HR) and cadence (revolutions per minute, rpm) were measured during field and laboratory trials, while oxygen uptake (V . O2) was determined only during the laboratory simulation. Results showed TT MTB racing is significantly shorter in duration and distance than XC racing and significantly higher for power output and heart rate, with more time spent above anaerobic threshold (16.0 +/- 2.4 and 22.8 +/- 4.3% time) and MPO (38.4 +/- 5.2 and 26.5 +/- 9.4% time) than XC racing (p<0.05). Mean power output and heart rate between the field and laboratory trials were similar (4.18 +/- 0.55 and 4.17 +/- 0.15 W/kg-1 respectively, 175 +/- 9 and 170 +/- 8 bpm). Time spent below 2 W/kg-1 and above 6 W/kg-1 for the field and laboratory trials accounted for ~32% and ~30% of the total time, respectively. During field and laboratory trials, cyclists utilised 77.8 and 77.3% of MPO, 93 and 90% of HRmax, respectively. There was a significant difference between mean cadence in the field and laboratory trials (60.3 +/- 9.1 and 75.2 +/- 7.0 rpm, respectively, p<0.05). The cadence band of 60-69 rpm showed a significant difference between the time spent in that band from the field (14.6%) to the laboratory (4.6%). The time spent above a cadence of 80 rpm in the field was 29.8% compared to the laboratory at 62.0% of the time. Mean and peak V . O2 for the simulation was 57.5 +/- 3.3 and 69.3 +/- 4.4 ml/kg-1/min-1 respectively, with cyclists sustaining an average of ~80% V . O2max. In summary, MTB competition requires multiple short-high intensity efforts and places high demands on both the aerobic and anaerobic energy systems. The power output and heart rate responses to a MTB field race are similar when simulated in the laboratory, although in the laboratory higher cadences are selected for the higher power outputs than the field.